Peace among Muslims - Zakyi Ibrahim (American Journal of Islam and Society, 2011)
Peace is seen as a sociopolitical value whose permanent realization keeps eluding humanity, despite constant efforts (at least for the past century) for it to prevail permanently. For Muslims, peace1 is not just a sociopolitical imperative; it is also a religious obligation. So any attempts to achieve it at anytime (be it among Muslims, or between them and their non-Muslim enemies) must be considered an act of obedience to God, who enjoined them, on several occasions in the Qur’an (for example, 8:61), to strive toward peace. In this editorial, I will highlight only peace among Muslims ...